Estrategia psicopedagógica basada en la gamificación para mejorar la compresión lectora en los estudiantes de Séptimo grado de la Unidad Educativa Pio Jaramillo Alvarado, periodo 2021-2022 - Mora Lozano, Manuel Alejandro (2023)
The present curricular integration work had as general objective to determine a psycho-pedagogical strategy based on gamification to improve the reading comprehension of Seventh grade students. The research was developed under the quantitative, non-experimental and cross-sectional approach; the PROLEC-R reading process evaluation battery applied to a sample of 31 parallel B seventh grade students was used. The results obtained in relation to the main indices show that students present slight difficulties in three of the reading processes; in the process of Identification of letters in the Equal-Different test with 65% of the students; in the lexical processes in the Word Reading test with 52% and in the semantic processes in the text comprehension test in the same way with 52% of the students. It is concluded in general terms that in relation to reading comprehension and the processes that are involved in reading, the majority of the investigated population is located in a light level difficulty, being the processes of identification of letters, lexical processes and semantic processes were the most affected. Based on the results, the psycho-pedagogical proposal based on gamification was designed to improve each of the reading processes involved in reading comprehension, a dynamic, motivating and creative proposal that leads to learning and interest in reading Keywords: PROLEC-R, gamification, reading comprehension, psychopedagogical strategies.